Map overlapping of QTL for resistance to Fusarium ear rot and associated traits in maize - Giomi, Gerardo Mario; Sampietro, Diego Alejandro; Velazco, Julio Gabriel; Iglesias, Juliana; Fernandez, Mariana; Oviedo, María Silvina (Springer, 2021)
Mapping QTL for disease resistance and associated traits is important to develop maize (Zea mays L.) hybrids less susceptible to ear rots. A biparental mapping population of 298 F5 recombinant inbreds (RIs), obtained from the cross between LP4637 (moderately resistant) and L4674 (susceptible), was genotyped with 250 single nucleotide polymorphism (SNP) markers. A set of 120 of those RIs, selected by uniRec procedure, and parental inbreds were phenotyped in two environments for pericarp thickness, pericarp content of trans-ferulic acid (tFA) and resistance to Fusarium ear rot. The set of parental inbreds exhibited an average density of one marker every 5 cM, 6% of a residual heterozygosity, and 5% of lost data. Moderate negative genotypic correlations were observed between disease severity and pericarp thickness (rG = − 0.31) and between disease severity and pericarp content of tFA (rG = − 0.32). Quantitative trait loci were mapped for disease severity in bins 1.06, 2.03, 3.06, 5.04, 5.07 and 6.05, for pericarp thickness in bins 1.06, 2.03, 4.02 and 4.05, and for pericarp content of tFA in bins 2.03, 3.06, 4.05 and 6.05. The joint models, including some additive-by-additive epistasis gene effects, explained 56.0–58.2%, 46.6–45.5%, 41.4–47.1% of the phenotypic variability for disease severity, pericarp thickness and pericarp content of tFA, respectively, depending on the environment. The most important QTL for the three traits overlapped in bin 2.03 indicating that genes from this genomic region might contribute to the expression of disease resistance by increasing thickness and tFA content of the pericarp.